"Speaking the Words": Linguistic Variation in the Pyramid Texts - Hainline, Brendan (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
This book investigates the linguistic diversity of the ancient Egyptian Pyramid Texts and what this diversity can reveal about the origins of the corpus and, more broadly, ancient Egypt in the Old Kingdom. It argues that the inclusion of linguistically diverse ritual utterances in the royal corpus of the Pyramid Texts was an intentional and active program by the royal court to incorporate ritual practices from the entire spectrum of Egyptian geography and society into the mortuary texts used by the king. The inclusion of ritual utterances representing all of Egypt thereby legitimized and monumentalized the authority of the king as the ruler of the totality of Egypt. In the book, the author describes the different categories of linguistic variation that exist in the Pyramid Texts. For each variant, there is a discussion of geographical, social, or chronological markers in the ritual utterances themselves that give clues as to where, when, or by whom that particular language variety would have been used. The author also draws on comparisons with Old Kingdom texts outside of the Pyramid Texts in order to map the distribution of the discussed linguistic variants throughout Egypt in order to produce a dialectical sketch of Old Kingdom Egypt. Additionally, this book situates the collection of the Pyramid Texts corpus into the historical context of the end of the Old Kingdom.